AB0172 PGC-1Α REGULATES AUTOPHAGY TO PROMOTE FIBROBLAST ACTIVATION AND TISSUE FIBROSIS. (2nd June 2020) - Zhang, Y.; Dreißigacker, K.; Distler, D.; Györfi, A. H.; Bergmann, C.; Zhou, X.; Shen, L.; Ludolph, I.; Horch, R.; Ramming, A.; Schett, G.; Distler, J.
Abstract : Background: Peroxisome proliferator-activated receptor gamma coactivator-1α (PGC-1α) is the best studied member of the family of coactivators. PGC-1α was initially identified through its interaction with PPARγ in brown adipose tissue. Recent evidence further indicates that PGC-1α may also modulate the transcription of autophagy-related genes, which has recently been shown to be required for fibroblast-to-myofibroblast differentiation under fibrotic conditions. However, the role of PGC-1α in the pathogenesis of SSc has not been investigated. Objectives: The aim of the present study was to evaluate the role of the coactivator PGC-1α on autophagy and to evaluate its role in the pathologic activation of fibroblasts in SSc. Methods: Expression of PGC-1α was analyzed by RT-PCR, Western blot and immunofluorescence. Modulation of autophagy was analyzed by reporter studies by expression of autophagy related genes. The effects of PGC-1α knockdown on collagen production and myofibroblast differentiation were analyzed in cultured human fibroblasts and in two mouse models with fibroblast-specific knockout of PGC-1α. Results: PGC-1α overexpression was detected by immunohistochemistry in skin sections of SSc patients and in experimental fibrotic murine skin, particularly in fibroblasts. Knockdown of PGC-1α inhibited the stimulatory effects of TGFβ on fibroblast activation with impaired induction of collagen as compared to control fibroblasts. Fibroblasts specific knockout of PGC-1α ameliorates experimental fibrosis in bleomycin-induced and adTBR-induced murine dermal fibrosis with decreased dermal thickness, hydroxyproline and myofibroblast counts compared to wild-type fibrotic mice. Incubation of dermal fibroblasts with TGFβ activated autophagy in control fibroblasts with increased expression of the autophagy-related genes ATG7 and BECLIN-1, enhanced conversion of LC3 I to LC3 II and decreased ratios of ILC3 I EGFP to LC3 II RFP in LC3 reporter assays. The expression levels of ATG7, BECLIN-1 and ILC3 II of TGFβ-stimulated PGC-1α knockout fibroblasts decreased compare to TGFβ stimulated wild-type fibroblasts. The ratio of ILC3 I EGFP to LC3 II RFP of TGFβ-stimulated PGC-1α knockout fibroblasts in reporter assays were comparable to unstimulated fibroblasts. Conclusion: PGC-1α is upregulated in SSc and promotes autophagy to foster TGFβ-induced fibroblast activation. Targeting of PGC-1α prevents aberrant autophagy, inhibits fibroblast activation and tissue fibrosis. References: [1]Finck BN, Kelly DP. PGC-1 coactivators: inducible regulators of energy metabolism in health and disease. The Journal of clinical investigation. 2006 Mar; 116(3):615-622 [2]Lindholm D, Eriksson O, Makela J, Belluardo N, Korhonen L. PGC-1alpha: a master gene that is hard to master. Cellular and molecular life sciences: CMLS. 2012 Aug; 69(15):2465-2468. [3]Li SY, Susztak K. The Role of Peroxisome Proliferator-Activated Receptor gamma Coactivator 1alpha (PGC-1alpha) in Kidney Disease. Semin Nephrol. 2018 Mar; 38(2):121-126. [4]Vainshtein A, Tryon LD, Pauly M, Hood DA. Role of PGC-1alpha during acute exercise-induced autophagy and mitophagy in skeletal muscle. American journal of physiology Cell physiology. 2015 May 1; 308(9):C710-719. [5]Zehender A LN, Stefanica A, Chen CW, Soare A, Wohlfahrt T, Rauber S, Bergmann C, Ramming A, Distler O, Schett G, Distler J. TGFβ Promotes Fibrosis By MYST1-Dependent Epigenetic Regulation of Autophagy [abstract]. Arthritis Rheumatol 2017; 69 (suppl 10). Disclosure of Interests: Yun Zhang: None declared, Katja Dreißigacker: None declared, Diana Distler: None declared, Andrea-Hermina Györfi: None declared, Christina Bergmann: None declared, xiang zhou: None declared, Lichong Shen: None declared, Ingo Ludolph: None declared, Raymund Horch: None declared, Andreas Ramming Grant/research support from: Pfizer, Novartis, Consultant of: Boehringer Ingelheim, Novartis, Gilead, Pfizer, Speakers bureau: Boehringer Ingelheim, Roche, Janssen, Georg Schett Speakers bureau: AbbVie, BMS, Celgene, Janssen, Eli Lilly, Novartis, Roche and UCB, Jörg Distler Grant/research support from: Boehringer Ingelheim, Consultant of: Boehringer Ingelheim, Paid instructor for: Boehringer Ingelheim, Speakers bureau: Boehringer Ingelheim